KONTRIBUSI RETRIBUSI DAERAH TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA SELATAN - Langi, Leonard (Sam Ratulangi University, 2014)
ABSTRACT: Region income is the thing very important in process region development. Any problem the big enough pasca region autonomy is dependence of region government in balancing finances from central government. The thing because weak of capability region government in manage potential in region for increasing them real income. Thus too with autonomy region South MinahasaRegencyÂ must have capability to dig the sources self finances, it manage and used to costing of implementation it region government included to benefit region retribution. Region retribution is region pickings be source region income South Minahasa Regency the potential, to costing carrying out implementation region government. See to be a direction of implementation this research to study and analyzed is with carrying out region retribution can give contribution to accepted PAD in South Minahasa Regency as soon as implementation decentralization be autonomous. In this research used descriptive research method, and the sample in this research is acceptance data region retribution years 2007 until with 2011. Sources this secondary data resulted from Finances Organizing Income and Assets Department South Minahasa Regency. In this analyzed to used formulas statistic descriptive, is analyzed presentation, average calculation, and least square analyzed. From the result this research has been point out the region retribution be any sector/source the real income from a region specially in region South Minahas Regencyhave contribution not significant to increasing acceptance PAD Finances Organizing Income and Assets Department South Minahasa Regency in 5 years latest 2007 until with 2011. For South Minahasa during estimate years 2007 until with 2011 region retribution in every years experience taking down in to give contribution to PAD. Keywords : contribution region retribution, acceptance the real income region.